Aplicacion de la metodologia Kaizen para incrementar la tasa de cierre, venta de productos conexos y satisfaccion del cliente prospecto del area de ventas de la empresa Autonort Trujillo S.A.C. - Alfaro López, Sergio Erick (2023)
The present work experience was carried out the process of selling new vehicles of the company Autonort Trujillo S.A.C. It was possible to identify that although the values of the KPIs of closing rate, sale of complementary products and prospect satisfaction are good, they can be improved by taking the average values of the Toyota dealer network as a reference. In this work, the Kaizen methodology was applied in order to clarify the current and ideal situation to identify the problem or gap, break down the problem, establish objectives, analyze root causes, develop and implement countermeasures, as well as monitor processes and results, to finally standardize successful processes or make appropriate adjustments. Applying this methodology, the result was an increase in the closing rate per listing from 6.1% to 7%, the closing rate per costumer from 7.3% to 8.5%, the sale of accessories from 22.7% to 39.1%, the sale of of LPG from 27.6% to 27.2%, the sale of MAF from 25.3% to 36.2% and the satisfaction of the prospect from 89% to 92%. In conclusion, the Kaizen methodology could be applied successfully, mapping the processes, performing statistical measurements, using the cause tree to analyze the root cause and implementing countermeasures, supported by the different tools used by industrial engineering, to later review effectiveness and standardize. The improvement in the indicators gave a great benefit to the company, as well as to the customers.